102k views
0 votes
2x + 2y = -4
3x - 2y = 9

User Theomax
by
4.8k points

2 Answers

1 vote

Final answer:

To solve this system of equations, multiply the first equation by 2 and the second equation by 2 to eliminate the y variable. Add the two equations together, divide by 10 to solve for x, and substitute x back into one of the original equations to solve for y. The solution is x = 1 and y = -3.

Step-by-step explanation:

To solve this system of equations:

  1. Start by eliminating the variable y. Multiply the first equation by 2 and the second equation by 2. This will give you:
  2. 4x + 4y = -8

  3. 6x - 4y = 18
  4. Add the two equations together to eliminate the y variable:
  5. 10x = 10
  6. Divide both sides by 10 to solve for x:
  7. x = 1
  8. Substitute the value of x back into one of the original equations. Let's use the first equation:
  9. 2(1) + 2y = -4
  10. Solve for y:
  11. 2 + 2y = -4

  12. 2y = -6

  13. y = -3
  14. The solution to the system of equations is x = 1 and y = -3.

User Eladian
by
5.1k points
3 votes

Answer:

x = −y −2

Step-by-step explanation:

User Tompave
by
6.0k points